Ebola virus inclusion bodies are liquid organelles whose formation is facilitated by nucleoprotein oligomerization - Bianca S. Bodmer; Melina Vallbracht; Dmitry S. Ushakov; Lisa Wendt; Petr Chlanda; Thomas Hoenen (Emerging Microbes and Infections, 2023)
Viral RNA synthesis of several non-segmented, negative-sense RNA viruses (NNSVs) takes place in inclusion bodies (IBs) that show properties of liquid organelles, which are formed by liquid–liquid phase separation of scaffold proteins. It is believed that this is driven by intrinsically disordered regions (IDRs) and/or multiple copies of interaction domains, which for NNSVs are usually located in their nucleo – and phosphoproteins. In contrast to other NNSVs, the Ebola virus (EBOV) nucleoprotein NP alone is sufficient to form IBs without the need for a phosphoprotein, and to facilitate the recruitment of other viral proteins into these structures. While it has been proposed that also EBOV IBs are liquid organelles, this has so far not been formally demonstrated. Here we used a combination of live cell microscopy, fluorescence recovery after photobleaching assays, and mutagenesis approaches together with reverse genetics-based generation of recombinant viruses to study the formation of EBOV IBs. Our results demonstrate that EBOV IBs are indeed liquid organelles, and that oligomerization but not IDRs of the EBOV nucleoprotein plays a key role in their formation. Additionally, VP35 (often considered the phosphoprotein-equivalent of EBOV) is not essential for IB formation, but alters their liquid behaviour. These findings define the molecular mechanism for the formation of EBOV IBs, which play a central role in the life cycle of this deadly virus.